Mesenchymal stromal cell based therapies for the treatment of immune disorders: recent milestones and future challenges. (1st February 2020) - Gonzalez-Pujana, Ainhoa; Igartua, Manoli; Santos-Vizcaino, Edorta; Hernandez, Rosa Maria
ABSTRACT: Introduction : Mesenchymal stromal cells (MSCs) present unique immunomodulatory properties that make them promising candidates for the treatment of inflammatory and immune disorders. MSC-mediated immunomodulation is a complex combination of mechanisms, in which the secretome plays a fundamental role. The plethora of bioactive molecules MSCs produce, such as indoleamine 2, 3-dioxygenase (IDO) or prostaglandin E2 (PGE2), efficiently regulates innate and adaptive immunity. As a result, MSCs have been extensively employed in preclinical studies, leading to the conduction of multiple clinical trials. Areas covered : This review summarizes the effects of some of the key biomolecules in the MSC secretome and the advances in preclinical studies exploring the treatment of disorders including graft-versus-host disease (GvHD) or inflammatory bowel disease (IBD). Further, late-stage clinical trials and the first MSC-based therapies that recently obtained regulatory approval are discussed. Expert opinion : Extensive research supports the potential of MSC-based immunomodulatory therapies. However, to establish the bases for clinical translation, the future of study lies in the standardization of protocols and in the development of strategies that boost the therapeutic properties of MSCs.